What is Lethe hyrania (Kollar, 1844) (Lepidoptera, Nymphalidae, Satyrinae)? - Lang, Song-Yun; Lamas, Gerardo (Zootaxa, 2016)
Known for a long time as "Lethe insana [sic] (Kollar, 1844)" (e.g. Fruhstorfer, 1911; D'Abrera, 1985), Lethe hyrania (Kollar, 1844) is a common, sexually-dimorphic, satyrine butterfly, found in the Sino-Himalayan region. Kollar (1844) described simultaneously both Satyrus isana and S. hyrania, as separate but closely related species, from northwestern India. Kollar (1844) spelt the name of the former in two different ways, as isana in the text (pp. 448, 449, 585), and as jsana in the legend for plate 16. Westwood (1851) maintained isana and hyrania as separate species but transferred them to the genus Debis Doubleday, whereas both Butler (1868) and Kirby (1871) assigned them to the genus Lethe Hübner, synonymizing isana under L. rohria (Fabricius). Moore (1882) was the first author to regard isana and hyrania as conspecific, the former representing the female sex and the latter the male, though he misspelt isana as "isania". Acting as First Reviser, Article 24.2 of ICZN (1999), Moore (1882) gave precedence to hyrania, thus the valid name for the species is Lethe hyrania. Later, Marshall & Nicéville (1883), Nicéville (1886), Doherty (1886), Elwes (1888), and Moore (1892) followed Moore's (1882) opinion, though afterwards Mackinnon & Nicéville (1897) argued that isana had priority over hyrania, based on "page precedence", ignoring Moore's (1882) previous action. Bingham (1905) was the first author to introduce the incorrect subsequent spelling "insana" and, apparently following Mackinnon & Nicéville (1897), also gave precedence to "insana" over hyrania. Most subsequent authors followed Bingham's (1905) error, and used Lethe "insana" for this species (for instance, Fruhstorfer, 1911; Evans, 1923, 1927; Gaede, 1931; Talbot, [1949]; Lesse, 1957; D’Abrera, 1985, 1990; Bozano, 1999). Except for Bozano (1999), who listed both hyrania and "insana" as valid species, without further comment, the name hyrania has been forgotten for over a hundred years.